DOI: 10.31274/etd-180810-3930
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Family Nutrition and Physical Activity screening tool and the Youth Activity Profile

Abstract: Childhood obesity affects one third of children and adolescents and is expected to increase in coming years. Obesity has been linked to both genetic and environmental factors with more recent research focusing on the role parents play in childhood obesity. The Family Nutrition and Physical Activity (FNPA) Screening tool was developed to provide practical ways to evaluate home obesogenic environments. However, no study to date has examined associations between FNPA scores and child behaviors. Therefore, the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…For example, one recent study reported that upper and lower limit of 95% CI for YAP predicted scores were within 10–20% of accelerometer-estimated scores [ 28 ]. The 5 questions on the “Chew” behavior were added upon the original validation of YAP, and showed small to moderate correlations ( r = 0.27) with a validated instrument for concurrent validity [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, one recent study reported that upper and lower limit of 95% CI for YAP predicted scores were within 10–20% of accelerometer-estimated scores [ 28 ]. The 5 questions on the “Chew” behavior were added upon the original validation of YAP, and showed small to moderate correlations ( r = 0.27) with a validated instrument for concurrent validity [ 29 ].…”
Section: Methodsmentioning
confidence: 99%